Produção e qualidade biológica de húmus de minhoca para uso na supressão de Sclerotium rolfsii Sacc - Zibetti, Volnei Knopp (2013)
The earthworm breeding corresponds to the creation of earthworm for different purposes like producing arrays and cocoons and worms for the production of vermicompost. The vermicompost, widely used as a fertilizer in agriculture and family farming systems ecologically based, also has important role as fitoprotetor. The study aimed to produce vermicompost of Eisenia andrei Bouché from cattle manure (CM) and combinations of this with peanut husk (PH), as structural materials, and spent coffee grounds (SCG), nutritional qualities of the source, and its evaluation in liquid and aerated form in suppressiveness Sclerotium rolfsii Sacc. The work was divided into two stages. At first, vermicompost produced up to four treatments and six replications: H1 CM 100%); H2 CM 75% + PH 25%; H3 CM 75% + SCG 25%; H4 CM 50% + SCG 25% + PH 25%. We evaluated the biomass of earthworms, cocoon production, yield and vermicompost microbiological and chemical variables. Treatments H3 and H4 had higher biomass and cocoon production. When assessed the density of bacterial colonies and fungal treatments H2 and H4 registered the highest rates. In the second step, vermicompost tea aerated were prepared from different combinations of vermicompost, in order to test their antagonistic effect against S. rolfsii. The vermicompost were packed in sachets and immersed in water and aerated for a period of 24 hours. Were quantified bacterial and fungal colonies present in vermicompost tea (VT), in selective culture media. Representative samples of VT obtained from each of the four treatments were evaluated on mycelial growth of S. rolfsii from mycelium and sclerotic under two conditions: unfiltered and filtered. The VT filtered did not inhibit mycelial growth of S. rolfsii, as opposed to VT unfiltered. Colonies of microorganisms coming from the unfiltered treatments, once isolated and purified, were paired with discs of mycelium of S. rolfsii, to evaluate the effect of antagonistic fungi and bacteria present in vermicompost on the sclerotic. The F3 isolated, on VT on treatment H2, identified as belonging to the genus Trichoderma, was the one who showed the greatest inhibition to S. rolfsii, among other microorganisms matched. The production and use of vermicompost in family farming should be encouraged, because besides the already established benefits of fertilization on cropping systems can also aid in the control of plant diseases.